Ex-cinema: “Ci devono essere delle macerie specifiche per costruire la città dell’impossibile”. Note su Eureka di Ernie Gehr - Rinaldo Censi (Cinergie, 2017)
One of the peculiar characters of hyperrealism can be seen in the tension that emerges from the transmission of data belonging to two channels of communication: photography-painting. As Lawrence Alloway stated in a text called “Photo-realism”, the hyperrealist artists paint in fact a double image: «The painting carries a reference to another channel of communication as well as to the depicted scene or object. The reality of photographs, however, is not the reality of slow, hand-done paintings, so that the realism of the subject matter is definitely called in doubt. It is as if the subject matter of, say, Eddy’s picture is not a Volkswagen but a photograph of a Volkswagen. The photograph corresponds to the car as we know it, but the painting corresponds as much to the photograph as to the car; it is, perhaps, the photograph that functions as the primary reference». The fact that each film carries the trace of its photographic matrix makes certain hyperrealist traits quite obvious. But is it possible that cinema allows a further hyperrealism, on a second degree? And has all this something to do with postproduction and ready-made?